Calabrian clan in Bollate, a particular ‘ndrangheta (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
The settlement’s model of the ‘ndrangheta in Bollate is a unicum that merged aspects of continuity and traits of novelty. As proved by previous researches, the preferential lines of ‘ndranghetista expansion are typical: the Milan hinterland confirms itself as the ideal setting for the mafia settlement strategies, rather than the town centre.The commingling between the mafia and local politics follows a logic of reciprocal convenience in the pursuit of shared interests; the subjection of the society to the mafia method emerges in particular in the local economy and in relation to specific professional categories (building contractors, local professionals ...). At the same time, the specific characteristics of the Bollate case differs from the "postulate" of 'ndranghetista colonization of previous community studies.Bollate is not the exclusive prerogative of a single Calabrian ‘ndrina. Two are the mafia realities that interact on the territory of the Lombard municipality: one from Guardavalle, the other from Rosarno. Two criminal dynasties that develop their genealogical branches on the municipal area. Two families that share their skills in the economy, both legal and illegal. Two main fields of interest: on the one hand private building and public procurement, on the other drug trafficking in continuous interaction with each other, according to the principle of mutual aid.A peculiar model of a Mafia settlement that enriches the presence of the 'Ndrangheta in Lombardy with new elements.